KERENTANAN EROSI DI DAERAH MANADO DAN SEKITARNYA, SULAWESI UTARA - Hidayat, S.; Suharsono, Suharsono (Jurnal Geologi dan Sumberdaya Mineral, 2007)
Evolution cycle of landform in Manado and surrounding area is  caused by  weathering, erosion, transportation, sedimentation, and human factors. These processes have occurred since the land existence, and theywere strongly accelerated   by human  activities.Based on slope level, soil/rock type, vegetation/land covers, and erosion type, the erosion susceptibility in the studied area can be grouped into: high, medium, low,  and no erosion.Very high erosion occurs  on landform  of volcanic cone a and  b, volcanic slope a and b, mountain  dissected volcanic slope and dissected straight  volcanic mountain. High erosion occurs on landform  of solfatara field, fumarola, volcanic foot slope b, volcanic mountain slope elongated  dissected, volcanic slope c, residual  hill and lava flow. Medium erosion occurs on landform of volcanic  foot slope a and alluvium  fan.  Lowerosion occurs on landform of volcanic  foot slope c, intermountain plane and flood plain. No erosion occurs on landform of alluvial.Keyword: erosion succeptibility, Manado, weathering, transportation, sedimentation